Isolation and functional characterization of hemp seed protein-derived short- and medium-chain peptide mixtures with multifunctional properties for metabolic syndrome prevention. (January 2023) - Cerrato, Andrea; Lammi, Carmen; Laura Capriotti, Anna; Bollati, Carlotta; Cavaliere, Chiara; Maria Montone, Carmela; Bartolomei, Martina; Boschin, Giovanna; Li, Jianqiang; Piovesana, Susy; Arnoldi, Anna; Laganà, Aldo
Graphical abstract: Highlights: Both SEC and UFM were applied for isolating short-chain peptides. More than 500 hemp seed short-chain peptides were identified. Hemp seed short-chain peptides exert multifunctional activities. Hemp seed peptides may be used for developing nutraceutical and functional foods. Abstract: This study aims to obtain a valuable mixture of short-chain peptides from hempseed as a new ingredient for developing nutraceutical and functional foods useful for preventing metabolic syndrome that represents the major cause of death globally. A dedicated analytical platform based on a purification step by size exclusion chromatography or ultrafiltration membrane and high-resolution mass spectrometry was developed to isolate and comprehensively characterize short-chain peptides leading to the identification of more than 500 short-chain peptides . Our results indicated that the short-chain peptide mixture was about three times more active than the medium-chain peptide mixture and total hydrolysate with respect to measured inhibition of the angiotensin-converting enzyme. The short-chain peptide mixture was also two times more active as a dipeptidyl peptidase IV, and twofold more active on the cholesterol metabolism pathway through the modulation of low-density lipoprotein receptor.